2000
DOI: 10.1111/j.1742-1241.2000.tb10912.x
|View full text |Cite
|
Sign up to set email alerts
|

Can Prophylactic Oral Erythromycin Reduce Time to Full Enteral Feeds in Preterm Neonates?

Abstract: SUMMARYEfficacy of oral, prophylactic erythromycin in reducing the time to establish full enteral feeds (150 ml/kg/day) was assessed in neonates <32 weeks, ready for enteral feeds. Seventy‐three consecutive neonates were randomised to receive oral erythromycin ethyl succinate (n=36) or placebo (n=37) in a double‐blind trial until full enteral feeds or 14 days of therapy were reached. A prospectively designed feeding regimen, including plan of action for signs of feed intolerance, was common for all enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…to 19 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and by 10 events in the placebo group to 19 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) per 24 hours (P ¼ 0.09). In addition, there was also no significant difference in acidic reflux (P ¼ 0.14), nonacidic reflux (P ¼ 0.46), proximal reflux (P ¼ 0.54), total reflux time (P ¼ 0.502), percent reflux time (P ¼ 0.86), bolus clearance time (P ¼ 0.49), or longest bolus clearance time (P ¼ 0.92) in the pre and post pH-MII studies of both treatment groups (Figs.…”
Section: Impedance Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…to 19 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and by 10 events in the placebo group to 19 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) per 24 hours (P ¼ 0.09). In addition, there was also no significant difference in acidic reflux (P ¼ 0.14), nonacidic reflux (P ¼ 0.46), proximal reflux (P ¼ 0.54), total reflux time (P ¼ 0.502), percent reflux time (P ¼ 0.86), bolus clearance time (P ¼ 0.49), or longest bolus clearance time (P ¼ 0.92) in the pre and post pH-MII studies of both treatment groups (Figs.…”
Section: Impedance Resultsmentioning
confidence: 98%
“…EES and placebo subjects had a median (interquartile range) number of pretreatment ABD events of 19 (9.5-26.25) and 16.5 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), respectively. ABD events decreased to 14 (4.75-19.5) in the EES group and to 10 (6-21) in the placebo group, which was not a statistically significant change (P ¼ 0.429) (Fig.…”
Section: Impedance Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other AEs of special interest in infants exposed to erythromycin include NEC and cardiac dysrhythmias. Previous randomized trials have demonstrated no significant differences in the incidence of NEC between infants treated with erythromycin and those given placebo (20)(21)(22)(23). Other studies found no increase in the incidence of cardiac arrhythmia, but sample sizes were small and evaluation for AEs was not performed in a systematic way, possibly resulting in a reduced event detection rate (20,23,26).…”
Section: Discussionmentioning
confidence: 98%
“…Despite this theoretical benefit, clinical trials evaluating the efficacy of erythromycin have demonstrated conflicting results. Sample size limitations, significant variability in timing of erythromycin initiation, either prophylactically or in response to clinical symptoms, and a wide range of recommended doses may explain the inconsistent results (16)(17)(18)(19)(20)(21)(22)(23). A double-blind, randomized controlled trial found benefit for 12 infants >32 weeks' gestation and no difference from placebo for 13 infants <32 weeks (16).…”
Section: Discussionmentioning
confidence: 99%